1992
DOI: 10.1073/pnas.89.17.8389
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of linkage disequilibrium in Rhizobium populations: evidence for sex?

Abstract: Many bacterial species exhibit strong linkage disequilibrium of their chromosomal genes, which apparently indicates restricted recombination between alleles at different loci. The extent to which restricted recombination reflects limited migration between geographically isolated populations versus infrequent mixis of genotypes within populations is more difficult to determine. We examined the genetic structure of Rhizobium kguminosarum biovar phaseoli populations associated with wild and cultivated beans (Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 34 publications
7
112
3
Order By: Relevance
“…For example, in Rhizobium etli associated to beans in the state of Morelos, Central Mexico, it was found that the less disturbed populations had less chromosomal recombination (they are more clonal), whereas the more intensively managed populations, have substantially more chromosomal recombination (2,22); similar patterns were found in other populations in the state of Puebla, also in Central Mexico (23). If these ideas are right, and plasmids travel with the rest of the chromosome, in the less managed populations there should be both very specific plasmid͞chromosome association and high linkage disequilibirum among chromosomal loci (Fig.…”
supporting
confidence: 52%
“…For example, in Rhizobium etli associated to beans in the state of Morelos, Central Mexico, it was found that the less disturbed populations had less chromosomal recombination (they are more clonal), whereas the more intensively managed populations, have substantially more chromosomal recombination (2,22); similar patterns were found in other populations in the state of Puebla, also in Central Mexico (23). If these ideas are right, and plasmids travel with the rest of the chromosome, in the less managed populations there should be both very specific plasmid͞chromosome association and high linkage disequilibirum among chromosomal loci (Fig.…”
supporting
confidence: 52%
“…Similarly, ecotypes inhabiting identical micro-niches in different locations are less likely to exchange DNA than clones from the same location. Evidence for this process has been found in the soil bacterium Rhizobium leguminosarum, where clonality was less pronounced at a regional scale than it was at a global scale (Souza et al, 1992).…”
Section: Selection Of Strainsmentioning
confidence: 99%
“…phaseoli strains that live in soils and in nodules of wild and cultivated beans [70]. In those studies, target organisms were generally isolated in pure cultures and their genotypic diversity was determined based on sequence analysis of protein-coding genes [74], multilocus enzyme electrophoresis [63], or genome-wide polymerase chain reaction (PCR) amplification of repetitive elements [11]. Pairwise genetic distances between genotypes were then inferred from DNA sequences or fingerprinting patterns between isolates, and clades obtained by cluster analyses were compared with the geographic origins of the isolates.…”
Section: Endemic Taxamentioning
confidence: 99%